From the Richmond Parkway to the Staten Island Greenbelt: The Rise of Ecological Zoning in New York City. (May 2017) - Nugent, Patrick
In the mid-1960s, the Staten Island Citizens Planning Committee (SICPC) thwarted plans for the Richmond Parkway, seeking instead to weave dense, affordable housing options within a network of linear preserves they donned "the Greenbelt." By the mid-1970s, however, the SICPC decoupled their environmental concerns from dense housing schemes, turning instead toward ecological zoning strategies. The SICPC's changing vision reveals the policies and park spaces that emerged when environmentalists ran square into the realities of the mid-1970s fiscal crisis. If such policies proved effective for preserving biodiversity, they also helped cement the segregated landscape taking shape across the metropolis.